Genome-Wide Identification, Characterization and Expression Analysis of the TCP Gene Family in Prunus mume - Zhou, Yuzhen; Xu, Zongda; Zhao, Kai; Yang, Weiru; Cheng, Tangren; Wang, Jia; Zhang, Qixiang (Frontiers in Plant Science, 2016)
TCP proteins, belonging to a plant-specific transcription factors family, are known to have great functions in plant development, especially flower and leaf development. However, there is little information about this gene family in Prunus mume, which is widely cultivated in China as an ornamental and fruit tree. Here a genome-wide analysis of TCP genes were performed to explore their evolution in P. mume. Nineteen PmTCPs were identified and three of them contained putative miR319 target sites. Phylogenetic and comprehensive bioinformatics analyses of these genes revealed that different types of TCP genes had undergone different evolutionary processes and the genes in the same clade had similar chromosomal location, gene structure, and conserved domains. Expression analysis of these PmTCPs indicated that there were diverse expression patterns among different clades. Most TCP genes were predominantly expressed in flower, leaf, and stem, and showed high expression levels in the different stages of flower bud differentiation, especially in petal formation stage and gametophyte development. Genes in TCP-P subfamily had main roles in both flower development and gametophyte development. The CIN genes in double petal cultivars might have key roles in the formation of petal, while they were correlated with gametophyte development in the single petal cultivar. The CYC/TB1 type genes were highly detected in the formation of petal and pistil. The less-complex flower types of P. mume might result from the fact that there were only two CYC type genes present in P. mume and a lack of CYC2 genes to control the identity of flower types. These results lays the foundation for further study on the functions of TCP genes during flower development.